The Routledge handbook of planning history. - (:unkn) unknown (Routledge, 2018)
The Handbook offers a comprehensive interdisciplinary overview of planning history since its emergence in the late 19th century, investigating the history of the discipline, its core writings, key people, institutions, vehicles, education, and practice. Combining theoretical, methodological, historical, comparative, and global approaches to planning history, The Routledge Handbook explores the state of the discipline, its achievements and shortcomings, and its future challenges. A foundation for the discipline and a springboard for scholarly research, the Handbook of Planning History explores planning history on an international scale in thirty-eight chapters, providing readers with unique opportunities for comparison. The diverse contributions open up new perspectives on the many ways in which contemporary events, changing research needs, and cutting-edge methodologies shape the writing of planning history.
Keywords: Planungstheorie; Planungsmodell; Geschichte; Stadtplanung; Stadtforschung; Raumplanung; Raumforschung; Planungsgeschichte; Planungsbegriff; Interdisziplinarität; Handbuch